Epulis and pyogenic granuloma with occlusal interference - Widowati Witjaksono; Ban Tawfeek Shareff Al Ani (Dental Journal (Majalah Kedokteran Gigi), 2005)
In dental clinic of Hospital University Science Malaysia (HUSM), there were cases with Localized Gingival Enlargement (LGE) in the oral cavity with occlusal interference. In this study, three cases were observed. They were a 13 - year- old female with fibrous lge around 31 and 32 with occlusal interference in protrusive movement due to X bite, a 15 - year – old female with pyogenic granuloma near 11 & 21 with occlusal interference due to deep bite; and a 24 – year – old female who was eight months in pregnancy with pyogenic granuloma on the 34-35 and severe generalized pregnancy gingivitis with occlusal interference in centric occlusion and lateral movement. Clinical and histopathological diagnosis of the first case showed fibrous epulis, whereas the second and third cases disclosed pyogenic granuloma. Chronic trauma of the gingiva due to occlusal interference was assumed to be the cause of those LGE in case 1 and 2, while in case 3 poor oral hygiene and chronic trauma were assumed to be the etiologic factors.